The relationship between environmental literacy, ecological literacy, and science for sustainability: A systematic literature review - H. Husamah; Abdulkadir Rahardjanto; Tutut Indria Permana; Nurdiyah Lestari (Research and Development in Education (RaDEn), 2025)
Global environmental changes driven by human behavior challenge sustainability, requiring environmental literacy (EL), ecological literacy (EcL), and science for sustainability (SfS) to foster awareness and evidence-based decisions, though their interconnections remain poorly understood. This study aimed to identify global research trends on EL, EcL, and SfS and explore their relationships in terms of subject areas, keyword distribution, thematic evolution, research instruments, sample populations, and materials. A systematic literature review (SLR) approach was applied, analyzing 11 articles retrieved from Scopus. Data visualization and analysis were conducted using VOSviewer, Rstudio/Biblioshiny, and the Scopus system. The findings highlight the dominance of social sciences, emphasizing the importance of social dimensions in sustainability research, followed by environmental sciences, which focus on ecological aspects. Contributions from agriculture, humanities, business, and engineering reinforce the need for a multidisciplinary approach. EL and sustainability emerge as central nodes, with key terms such as environmental education, learning, and ecology strengthening their link to education. Ecology education, domestic waste, critical theory, and action research indicate broader applications beyond formal education. Research in this domain is evolving, integrating education, technology, and behavioral sciences to develop innovative sustainability solutions.